EXPLORING THE MECHANISM AND PATH OF THE REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) FOR ECONOMIC INNOVATIVE DEVELOPMENT (POINT OF VIEW WITH SYSTEM DYNAMICS MODEL) - Sundiman, Didi; Fatma Satyani; Angelina Halim, Michelle; Kristina, Nerry (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Universal., 2025)
This research aims to address gaps by conducting a detailed analysis of the RCEP's provisions and their expected impact on innovation, using both qualitative and quantitative methods with System Dynamics to offer a nuanced understanding of the RCEP's innovation potential. The research design used a qualitative analysis to examine the impact of the Regional Comprehensive Economic Partnership (RCEP) on economic innovation. As useful tools, System Dynamics help identify potential challenges, such as trade imbalances or sector-specific vulnerabilities, enabling more informed policy decisions. Our research on the RCEP explored its provisions related to trade, investment, and intellectual property. These specific clauses directly impact economic innovation by promoting technology transfer, harmonizing standards, and facilitating cross-border collaboration. Through a System Dynamics perspective, we modeled how these provisions translate into actionable strategies. Our dynamic simulations revealed how changes in one area (e.g., increased technology transfer) ripple through the system, affecting other variables (e.g., R&D investments, market access). By understanding these interdependencies, member countries can develop targeted policies and investment plans. Anticipated impacts of RCEP on innovative capacities extend beyond economic growth, shaping the long-term competitiveness of the region.